Innovative Digital Pedagogies in Mathematics and Science Learning - Sry Wahyuni Zandri; Arnelis; Suherman; Yuliyanti Harisman; Yerizon (Postgraduate, University of Mataram, 2025)
This study reviews innovative digital pedagogies integrated into mathematics and science classrooms, focusing on tools such as virtual simulations, dynamic geometry software, augmented reality, mobile applications, flipped classrooms, and intelligent tutoring systems. The purpose is to examine their impact on student engagement, conceptual understanding, and pedagogical effectiveness. Findings indicate that these digital tools enhance interactivity and learner autonomy, promote deeper conceptual understanding through visualization and feedback, and increase student motivation and participation. Adaptive technologies that provide personalized feedback show promise in matching the effectiveness of human tutoring. However, technology alone does not guarantee improved learning outcomes; effective integration requires intentional pedagogical design aligning content, pedagogy, and technology. Challenges include infrastructure limitations and educational inequity, particularly in under-resourced regions. Additionally, a shift in the teacher’s role toward facilitator and designer of learning experiences is critical.